2023
DOI: 10.3390/cryst13040700
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Band Gap Variation in InGaN/GaN Short Period Superlattices

Abstract: The use of strained substrates may overcome indium incorporation limits without inducing plastic relaxation in InGaN quantum wells, and this is particularly important for short-period InGaN/GaN superlattices. By incorporating elastic strain into these heterostructures, their optoelectronic behavior is modified. Our study employed density functional theory calculations to investigate the variation in the band-gap energy of short-period InGaN/GaN superlattices that comprise pseudomorphic quantum wells with a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We evaluated the evolution of the electronic band gap by introducing a biaxial tensile strain, as experimentally reported for GaN grown on sapphire. ,, Eight different biaxial strains up to 1.01% were evaluated, and in this range, we observed a perfect linear correlation between the band gap and the induced strain (see Figure S4). A theoretical band gap of 3.27 eV was obtained which is in excellent agreement with other theoretical studies. The observed changes in band gap are in line with previous studies reported by Chatzopoulou et al in which E g decreased 5.4% (3.28 to ∼3.1 eV) when applying a 1.5% biaxial strain. In comparison, we observed a reduction of 7.4% for a similar biaxial strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the evolution of the electronic band gap by introducing a biaxial tensile strain, as experimentally reported for GaN grown on sapphire. ,, Eight different biaxial strains up to 1.01% were evaluated, and in this range, we observed a perfect linear correlation between the band gap and the induced strain (see Figure S4). A theoretical band gap of 3.27 eV was obtained which is in excellent agreement with other theoretical studies. The observed changes in band gap are in line with previous studies reported by Chatzopoulou et al in which E g decreased 5.4% (3.28 to ∼3.1 eV) when applying a 1.5% biaxial strain. In comparison, we observed a reduction of 7.4% for a similar biaxial strain.…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical band gap of 3.27 eV was obtained which is in excellent agreement with other theoretical studies. 35−37 The observed changes in band gap are in line with previous studies reported by Chatzopoulou et al 38 in which E g decreased 5.4% (3.28 to ∼3.1 eV) when applying a 1.5% biaxial strain. In comparison, we observed a reduction of 7.4% for a similar biaxial strain.…”
Section: ■ Introductionmentioning
confidence: 99%